Behavioural Disorders & Implementation of Homoeopathy Medicines (Homoeopathy for All, 2024)
In later childhood stage the  psychological complaints, such  as apprehension, despondency  and PTSD (post-traumatic stress  disorder) inclined to occur. Mostly  these are hard to be identified  initially by the guardians or the  others as some babies have not  originated significant vocabulary  and cognition to demonstrate their  feelings.
Keywords: Behavior disorder; Conduct disorder; Anxiety; Depression etc